RESULTS OF ADMINISTRATION OF COMBINED VACCINE AGAINST DIPHTHERIA, PERTUSSIS, TETANUS, POLIOMYELITIS AND HAEMOPHILIC INFECTION TYPE B IN CHILDREN WITH CONCOMITANT DISEASES - N. F. Snegova; L. V. Pushko; T. Yu. Illarionova; O. A. Salkina; Yu. V. Smirnova ("Paediatrician" Publishers LLC, 2011)
The article summarizes data on methods and opportunities of frequently ailing children rehabilitation. Authors mark a leading role of vaccination against pneumotropic infections. Questions of successful interaction between doctor and frequently ailing child's parents are highlighted. The observation of 94 children 3 months - 3 years old (patients had different types of initial immune insuffiiency, neurological pathology, recurrent obstructive bronchitis, or were included in group of frequently ailing children) vaccinated with Pentaxim was performed. 94% of children showed asymptomatic postvaccinal period. Fever up to 39°C occurred in 2.3% of patients. Local reactions (diameter was not over 3-5 cm) developed in 1.7% of children. There was no any case of postvaccinal complication. Evaluation of vaccine's reactogenity proves its safety and reasonability in immunization against pertussis, diphtheria, tetanus, poliomyelitis, Haemophilis influenzae type b in children of different health state including those with concomitant diseases.